COMPARATIVE STUDY FOR EDGE DETECTION OF NOISY IMAGE USING SOBEL AND LAPLACE OPERATORS - Instructor Sameera A. Abdul-Kader Asst. lecturer Aadel I. Khalil (College of Education for Women, 2019)
Many approaches of different complexity already exist to edge detection in color images. Nevertheless, the question remains of how different are the results when employing computational costly techniques instead of simple ones. This paper presents a comparative study on two approaches to color edge detection to reduce noise in image. The approaches are based on the Sobel operator and the Laplace operator. Furthermore, an efficient algorithm for implementing the two operators is presented. The operators have been applied to real images. The results are presented in this paper. It is shown that the quality of the results increases by using second derivative operator (Laplace operator). And noise reduced in a good range by using mean filter for smoothing before applying Laplace operator. Moreover, thresholding is used for image in both cases to see results in clearer manner.